Analysis Of Raw Material Supply In Smes With Using The Economic Order Quanti Ty(EOQ) Method (Case Study in Dinfood_Bdl Culinary Business) - Andini Parastika; Iskandar Ali Alam (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to analyze whether the inventory system used by the company has reached maximum and effective figures, which can then be used as a consideration for Dinfood_bdl to be applied as a basis for procurement of inventory. This research method is descriptive qualitative. The data that will be collected by researchers is based on information obtained when meeting directly with informants. Primary data was obtained from observations and interviews with research subjects. This research also has the result that through the application of the EOQ method the ordering costs incurred by the company during one period are smaller compared to the method used by the company. This is because by using the EOQ method the order frequency for one period is less than that applied by the company, namely 12 times, while the order frequency based on the EOQ method requires ordering 9 times. This is because the company does not want to take the risk of running out of raw material supplies and wants to maintain a high level of inventory to ensure the production process can continue. From the inventory cost analysis, Dinfood_bdl can apply the time and quantity of purchases of production materials